Nighttime Image Enhancement: A Review of Topical Concepts - Basheer, Ola; Al-Ameen, Zohair (Sistemasi: Jurnal Sistem Informasi, 2024)
With the increasing spread of nighttime images and their importance in human lives, and the development of computer vision, producing images with the highest possible quality is paramount. Nighttime images have been improved over the past decades by introducing many methods, each of which uses different techniques to enhance the quality of such images that have many degradations, such as poor illumination, uneven lighting, low contrast, widespread noise, and unnatural colors. This paper reviews twelve modern-day algorithms that can be used to enhance nighttime images by presenting the concepts, work mechanisms, processing abilities, and performance evaluations for each algorithm. Likewise, these algorithms are evaluated using three metrics with their processing times, and the advantages and disadvantages of each algorithm are given. Such a review can help researchers understand which concepts to select for development, which drawbacks to avoid when developing an algorithm in this field, and what the currently available concepts are.